Room temperature CO sensing by polyaniline/Co3O4 nanocomposite. Issue 42 (13th July 2016) - Sen, T.; Shimpi, N. G.; Mishra, S.
ABSTRACT: Polyaniline/cobalt oxide (PANI/Co3 O4 ) nanocomposites have been investigated for their sensitivity towards carbon monoxide (CO) gas at room temperature. The Co3 O4 nanoparticles were prepared by ultrasound assisted coprecipitation method and then incorporated into the PANI matrix. Fourier transform infrared spectroscopy and ultraviolet–visible spectroscopy, powder X‐ray diffraction, and field emission scanning electron microscopy have been used to characterize the nanomaterials. The PANI/Co3 O4 nanocomposite sensors were found to be highly selective to CO gas at room temperature. A significantly high response of 0.81 has been obtained for 75 ppm CO concentration with a response time of 40 s. Based on the observations of the sensing study, a mechanism for CO sensing by the nanocomposite has been proposed. Influence of humidity on the sensor response towards CO has also been studied and the results presented. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44115. Abstract :